Impact of EcSOD Perturbations in Cancer Progression - Brianne R. O'Leary; Rory S. Carroll; Garett J. Steers; Jennifer Hrabe; Frederick E. Domann; Joseph J. Cullen (MDPI AG, 2021)
Reactive oxygen species (ROS) are a normal byproduct of cellular metabolism and are required components in cell signaling and immune responses. However, an imbalance of ROS can lead to oxidative stress in various pathological states. Increases in oxidative stress are one of the hallmarks in cancer cells, which display an altered metabolism when compared to corresponding normal cells. Extracellular superoxide dismutase (EcSOD) is an antioxidant enzyme that catalyzes the dismutation of superoxide anion (O2−) in the extracellular environment. By doing so, this enzyme provides the cell with a defense against oxidative damage by contributing to redox balance. Interestingly, EcSOD expression has been found to be decreased in a variety of cancers, and this loss of expression may contribute to the development and progression of malignancies. In addition, recent compounds can increase EcSOD activity and expression, which has the potential for altering this redox signaling and cellular proliferation. This review will explore the role that EcSOD expression plays in cancer in order to better understand its potential as a tool for the detection, predicted outcomes and potential treatment of malignancies.